Chronic pain experiences of immigrant Indian women in Canada: A photovoice exploration - Nida Mustafa; Shreeyaa Ramana; Margaret MacNeill; Judy Watt-Watson; Gillian Einstein (Taylor & Francis Group, 2024)
Background Over the past two decades, the prevalence of chronic pain has significantly increased globally, with approximately 20% of the world's population living with pain. Although quantitative measures are useful in identifying pain prevalence and severity, qualitative methods, and especially arts-based ones, are now receiving attention as a valuable means to understand lived experiences of pain. Photovoice is one such method that utilizes individuals' own photography to document their lived experiences.Aims The current study utilized an arts-based method to explore immigrant Indian women's chronic pain experiences in Canada and aimed to enhance the understanding of those experiences by creating a visual opportunity for them to share their stories.Methods Twelve immigrant Indian women captured photographs and participated in one-on-one interviews exploring daily experiences of chronic pain.Results Women's photographs, and description of these photographs, provided a visual entry into their lives and pain experiences. Three themes emerged from our analysis: (1) bodies in pain, (2) traversing spaces including immigration, and (3) pain management methods. Findings revealed that women's representations of pain were shaped by a clash between culturally shaped gender role expectations and changing gender norms due to immigration processes. The use of photovoice visually contextualized and represented pain experiences, proving to be a valuable tool for self-reflection.Conclusions This research uncovers the multifaceted nature of chronic pain and identifies the influence of immigration, gender, and social relations on the exacerbation of pain in immigrant Indian women.